Effects of Multimodal Rheumatologic Complex Treatment in Childhood and Adolescence - Katharina Kreilinger; Regina Huehn; Jessica I. Hoell; Andreas Wienke; Katja Raberger (Children)
Background: The aim of this study was to investigate the effects of multimodal rheumatologic complex treatment (MRCT) in childhood and adolescence. MRCT means a high-frequency treatment program of at least 11 h per week. Methods: MRCTs in children, carried out between May 2009 and May 2022 at the Department of Pediatrics of the University Hospital in Halle (Saale), were included in this study. The effects of the MRCT were evaluated based on inflammatory activity, functionality (using the Childhood Health Assessment Questionnaire (CHAQ)), subjective statements regarding pain intensity, state of health, and coping with the illness, as well as the objective determination of joint mobility. Data were analyzed retrospectively using t-tests to compare different groups and values before and after treatment. Results: During the study period, N = 133 MRCTs were conducted in n = 95 children. The most common diagnosis was juvenile idiopathic arthritis (83.2%). The c-reactive protein (CRP) fell from an average of 25.3 mg/L to 7.3 mg/L, and the erythrocyte sedimentation rate (ESR) fell from 29.5 mm in the first hour to 17.9 mm. Pain intensity was reduced from 5.4 to 4.0. The state of health and coping with the illness also improved. The disability index showed a moderate reduction from 0.92 to 0.81. Furthermore, an improvement in joint mobility was observed. Positive effects were also shown in patients with somatoform disorders. Conclusions: Due to the positive effects of MRCT on subjective well-being and physical health, the treatment program can be recommended for affected children, including patients with an additional diagnosed somatoform disorder.